Analisis Deiksis Sosial Sebagai Representasi Aspek Sosial Dalam Novel Memang Jodoh Karya Marah Rusli - Oktaviani, Anisa Dara (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to find out how social deixis represents social aspects in the novel Indeed Jodoh by Marah Rusli by using social deixis theory from Levinson (1983) and supported by the results of Stockwell's research (2020) regarding elements of social deixis to produce broader social aspects. This type of research is descriptive qualitative with the sociology of literature method which examines the relationship of literature with social aspects. Therefore, the social aspects used refer to aspects of the sociology of literature put forward by Löwenthal, namely social class, love, work, religion, nature, and art. Deictic expressions that represent social aspects are collected, then classified, and analyzed. The total social deictic expressions found were 232: 68 aspects of social class, 65 aspects of love, 35 aspects of religion, 27 each of work and nature aspects, and 10 aspects of art. The high number of aspects of social class and love shows that this novel raises the issue of social class and class conflict which is illustrated by resistance to arranged marriage culture. The research results also show that social deixis can help readers better understand the essence of a literary work.